EXTRACTION AND ANTIOXIDANT ACTIVITY OF Carissa carandas SEED OIL - relv; Pham Xuan Len; Nguyen Thi Kieu Diem; Hoang Quoc Toan; Tran Le Tan Tien (HUIT Journal of Science, 2025)
In this work, Soxhlet and ultrasonic extraction were used to successfully extract oil from Carissa carandas seeds cultivated in Ben Tre province, Vietnam. According to the results of the solvent survey, the n-hexane solvent provided high extraction efficiency and high-quality oils. Oil yields were 6.57% after six hours of Soxhlet extraction and 6.69% after one hour of ultrasonic extraction. The study found that adopting ultrasonic extraction technology can assist in minimizing extraction time while maintaining oil quality and production. Carissa carandas oil has a refractive index of 1.4568 and a specific gravity of 0.8680 g/cm3, representing seed oil. The antioxidant activity testing using the DPPH method revealed that the oil concentration of 19.4 mg/mL was capable of inhibiting 50% of DPPH free radicals. Therefore, Carissa carandas seed oil has potential applications in food and cosmetics.